Analisis Pengambilan Keputusan Strategis dalam Manajemen Pendidikan di Sekolah Dasar: Sebuah Tinjauan Literatur - Ardi Ansah Rambe; Zarkasih Efendi; Muhammad Syaifuddin (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
Strategic decision-making is crucial in determining the quality and sustainability of elementary schools. However, school administrators often face challenges such as limited human resources, underutilization of data, and insufficient stakeholder engagement. This study aims to provide a systematic, in-depth, and comprehensive overview of the concepts and implementation of strategic decision-making in elementary school education management. The method used is descriptive qualitative research through a literature review, examining relevant books, scientific journals, and academic documents. The strategic decision-making process includes the stages of problem identification, data collection through SWOT analysis, formulation of alternatives, implementation, and periodic evaluation. There are three models of approach that can be applied: the classical, administrative, and incremental models. In the context of elementary schools, principals make decisions through deliberation mechanisms, incorporating input from various sources, and utilizing intuition. Principals’ strategic decision-making directly impacts the quality of institutional management. A democratic-participatory leadership approach has proven more effective in achieving shared goals. Principals are advised to enhance their data-driven decision-making capabilities and strengthen synergy with all stakeholders.